Menanamkan Pendidikan Karakter Melalui Media Augmented Reality Animasi Dua Dimensi Lakon Dewa Ruci kepada Remaja - Dwiki Setya Prayoga; I Nyoman Lodra; Autar Abdillah (Rekam : Jurnal Fotografi, Televisi, Animasi, 2020)
Implanting Character Education Values through the Augmented Reality of Two-Dimensional Animation of Dewa Ruci to Teenagers. Teenagers are the next generation for the nation and country. However, teenagers tend to have bad behaviors and act out of control that can threat the nation and the country, such as being involved in a fight, violence, drug abuse, alcohol addict, and even free sex. It is very important to instill the values of character education to the teenagers such as honesty, mutual respect, courtesy, and perseverance. Character education is often related to culture with regards to the mind and common senses. This is because human's life cannot be separated from culture and the traditions. One of the cultural things is wayang (shadow puppetry).  Shadow puppetry is a symbol of human beings and the shadow of their humanity. Lakon Dewa Ruci (Dewa Ruci play) tells a story of a student who is obedient to his teacher.  As implied in the story, a student is supposed to be obedient to his teacher, while the teacher must be discipline yet patient in dealing with the students. A teacher with his responsibility in education is demanded to enhance  his quality and his expertise. In the effort to educate the life of a nation, the role of technology is needed in order to make the teenagers have a broader knowledge as well as to have an interest and a passion to keep learning.   Nowadays animated videos are often preferred by the teenagers in general, not to mention in the field of education. Animation has become media or instruments to deliver the most updated information.  Evaluation conducted in this research had used a questioner and the result showed 98% for the media quality from the material aspects and for the post test obtained 63%.  Therefore, the results could define whether this product of animation is eligible, or in other words, no revision is needed.  ABSTRAK Remaja merupakan generasi penerus bagi bangsa dan negara. Namun, remaja juga berpotensi mempunyai perilaku buruk dan di luar kendali yang dapat mengancam bangsa dan negara, seperti perkelahian, kekerasan, penyalahgunaan narkoba, minuman keras, dan seks bebas. Sangat penting untuk menanamkan nilai-nilai pendidikan karakter kepada remaja seperti kejujuran, saling menghormati, sopan santun, dan pantang menyerah. Pendidikan karakter sering dikaitkan dengan kebudayaan yang berhubungan dengan budi dan akal manusia. Hidup manusia tidak lepas dari kebudayaan dan adat istiadat. Salah satu contoh kebudayaan adalah wayang. Wayang merupakan simbol manusia dan bayangan dari kemanusiaan itu sendiri. Lakon Dewa Ruci bercerita tentang murid yang patuh kepada gurunya. Sebagai murid hendaknya menghormati gurunya, sedangkan guru hendaknya tegas dan sabar dalam menghadapi muridnya. Guru dalam dunia pendidikan dituntut untuk meningkatkan kualitas dan mutunya. Dalam upaya mencerdaskan kehidupan bangsa, peranan teknologi sangat diperlukan supaya remaja memiliki wawasan yang luas serta dapat memiliki minat dan ketertarikan untuk terus tetap belajar. Saat ini video animasi seringkali digemari oleh remaja umumnya apalagi dalam dunia pendidikan. Animasi digunakan sebagai media atau alat untuk menyampaikan informasi yang lebih terkini. Evaluasi yang dilakukan dalam animasi ini menggunakan angket dan diperoleh hasil uji kualitas media aspek materi mendapatkan hasil 98% dan pada post test mendapatkan hasil 63%. Dari data angket tersebut dapat dikatakan produk ini layak dan tidak perlu direvisi.